PENGALAMAN PADA PEGAWAI YANG MENGALAMI PEMOTONGAN GAJI DI MASA PANDEMI COVID-19 - Michelle Elfreda Juangta (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Abstract : Concern for the quality of life (quality of life) is the center of attention in the current state of the pandemic. Changes in the environment cause attention to be focused on the quality of life. In this study, the researcher will use qualitative methods so that this event can be understood without any theoretical limitations that separate the reader from the subject, but the reader can also feel, appreciate, and seem to be in the life of the subject. Through qualitative methods, events can be seen from the perspective of the author and the research subject. In this study, the research results were grouped into three main categories of responses as employees working during Covid-19. The first category is employees who feel dissatisfied with their situation since Covid-19, the second category is employees who feel dissatisfied with their situation but are still trying to accept it since Covid-19, while the last category is the category of employees who feel fine and supportive. the course of company policies during the Covid-19 pandemic. This study has answered the research question that EWB is very important for working employees, because EWB affects work engagement and motivation. Decreased work motivation will affect the way employees work as well. Income is thought to be one of the factors that affect welfare because everything does require money. However, EWB can still be fulfilled during this Covid-19 pandemic even though there is a decrease in income.